Changes in virus detection in hospitalized children before and after the severe acute respiratory syndrome coronavirus 2 pandemic. Issue 5 (29th April 2022) - Kume, Yohei; Hashimoto, Koichi; Chishiki, Mina; Norito, Sakurako; Suwa, Reiko; Ono, Takashi; Mochizuki, Izumi; Mashiyama, Fumi; Ishibashi, Naohisa; Suzuki, Shigeo; Sakuma, Hiroko; Takahashi, Hitoshi; et al.
Abstract: The impact of strengthening preventive measures against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection on the prevalence of respiratory viruses in children was examined. After the SARS‐CoV‐2 pandemic, the rate of multiple virus detection among hospitalized children decreased. Immediately after the SARS‐CoV‐2 pandemic, respiratory syncytial and parainfluenza viruses were rarely detected and subsequently reemerged. Human metapneumovirus and influenza virus were not consistently detected. Non‐enveloped viruses (bocavirus, rhinovirus, and adenovirus) were detected to some extent even after the pandemic. Epidemic‐suppressed infectious diseases may reemerge as susceptibility accumulates in the population and should continue to be monitored.